Principal’s Performance in Improving the Quality of Educators - Suranto, Andi (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
This study aims to identify, describe and analyze the performance of school principals in improving the quality of teaching staff at SMA Negeri 3 Kayuagung, Ogan Komering Ilir district, and to identify and describe the efforts and factors that influence the performance of school principals in improving the quality of teaching staff at Kayuagung 3 Public High School, Ogan Komering Ilir Regency. This study, a qualitative descriptive one, was conducted at SMA Negeri 3 Kayuagung in the Ogan Komering Ilir Regency. Data was gathered through observation, interviews, and documentation. The study’s findings indicate that: 1. The principal’s performance has generally been excellent, meeting the established standards and indicators. This is described in the school work plan (RKS) as the principal’s strategy for implementing work programs and hiring more teachers. 2) The principal’s effectiveness in raising the caliber of teachers is influenced by a number of variables, including the school’s geographic location, the qualifications of the teaching staff, and a supportive environment. 3) The principal has worked to raise the caliber of educators through empowerment initiatives and educational initiatives like supervision, MGMP, self-evaluation (EDS), in-house training (IHT), and entrepreneurship programs for educators and students.